Islamic Financial Literacy: Evidence From Indonesian Urban Middle-Class Women - Alfina Rahmatia; Andy Putra Wijaya; Arief Dwi Saputra; Muhammad Imam Ma’ruf (Journal of Islamic Economic Laws, 2022)
Issues related to Islamic financial literacy are always interesting to study, mainly because financial literacy has a close relationship with inclusive finance, including women's intelligence which is often questioned in terms of financial literacy. As if only women are the only gender whose abilities and intelligence are always questioned. The paradigm of women is being left behind as if it has been ingrained in some Indonesians. This study uses an explanatory sequential mixed method, in which qualitative data is taken from the study literature, then analyzed using the Nvivo 12 application. Quantitative data is taken from a questionnaire, then analyzed using the SPSS application. The result from qualitative data analysis would explain more the findings. This study proves that gender does not affect financial literacy, it can be said that women in Indonesia urban middle-class are not left behind. Everyone has the same rights in learning about Islamic financial literacy.